2011
DOI: 10.1016/j.ijid.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

First case of Legionella pneumophila native valve endocarditis

Abstract: We report the first case in the English language literature, to our knowledge, of native valve endocarditis due to Legionella pneumophila. The patient had no prior history of cardiothoracic intervention or congenital valvular process. A transesophageal echocardiogram showed a vegetation on the aortic valve. Blood culture and bronchoalveolar lavage returned positive for L. pneumophila. The patient was treated with levofloxacin for 6 weeks total after a second set of blood cultures were negative. The patient sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
10
1
Order By: Relevance
“…All but one of the endocarditis cases occurred in patients who had received aortic homografts or prosthetic valve replacements, and in most cases, the suspected route of infection was via direct inoculation with contaminated surgical equipment. The single case of native valve endocarditis reported in the literature was due to L. pneumophila (18). In contrast, 16S rRNA PCR and sequencing of the aortic value tissue and culture isolate in our case revealed that the Legionella strain, designated H63, shared the highest similarity with L. brunensis ATCC 43878 T (98.4%), an environmental strain originally isolated from a cooling tower in Czechoslovakia and never implicated in disease (23 T (96.0%).…”
contrasting
confidence: 61%
See 1 more Smart Citation
“…All but one of the endocarditis cases occurred in patients who had received aortic homografts or prosthetic valve replacements, and in most cases, the suspected route of infection was via direct inoculation with contaminated surgical equipment. The single case of native valve endocarditis reported in the literature was due to L. pneumophila (18). In contrast, 16S rRNA PCR and sequencing of the aortic value tissue and culture isolate in our case revealed that the Legionella strain, designated H63, shared the highest similarity with L. brunensis ATCC 43878 T (98.4%), an environmental strain originally isolated from a cooling tower in Czechoslovakia and never implicated in disease (23 T (96.0%).…”
contrasting
confidence: 61%
“…A request for an autopsy was declined. (2,5,6,10,11,13,15,18,20). All but one of the endocarditis cases occurred in patients who had received aortic homografts or prosthetic valve replacements, and in most cases, the suspected route of infection was via direct inoculation with contaminated surgical equipment.…”
mentioning
confidence: 99%
“…Only 16 cases have been reported from which the first is dated to 1984 [7]. In almost all cases patients had experienced valve surgery, only two other cases besides ours had native valves [8,9]. In our case the urinary und serum analyses for Legionella antigen was positive, but specific PCR for Legionella as well as was broad spectrum PCR showed repeatedly negative results.…”
Section: Discussionmentioning
confidence: 58%
“…In our case the urinary und serum analyses for Legionella antigen was positive, but specific PCR for Legionella as well as was broad spectrum PCR showed repeatedly negative results. In literature only in one patient the diagnosis was confirmed with PCR and sequencing from aortic tissue [9], in the other, Legionella pneumophila serotype 1 was detected in the urine sample and cultures on buffered charcoal-yeast extract (BCYE)-Agar using blood and bronchial fluid [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation